Flexibility of labor laws with the advent of neoliberalism (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The emergence of neoliberalism, primarily from the 1970s onwards, coincided with the crisis of the welfare state and triggered a series of profound transformations in the landscape of work. These structural changes ushered in a new production paradigm, a diminished role of the state, growing individualism, and an expanded focus on capital accumulation. All of these characteristics resonate with the core of the capitalist model. This article aims to elucidate the historical process that enabled these changes and demonstrate the influence of this new context on the flexibilization of labor laws, including the Brazilian Labor Reform of 2017, which legitimized the increasing precarization of working conditions in the contemporary world.